Quero rugby: como o design pode auxiliar na difusão do rugby no estado do Rio Grande do Sul - Albara, Jeferson (My University, 2020)
Rugby is a very popular spore, but it has not yet managed to establish itself in Brazil, despite the recent numbers that show a growing, this evolution and expansion still walks in a very primary way, not exploring all the sport's capacity. Having enormous growth potential to become something to be integrated into the Brazilian sports culture. The expansion of the sport aims to integrate all social classes, genders and biotypes of all ages being a perfect sport to keep the body and mind healthy, besides providing fun, well-being, and helping in the physical and mental development, the sport offers a high degree of competition for the most energetic athletes. This is a work equipped with the fermentes of strategic design and aims to disseminate and create a bridge that brings rugby closer to people, making the sport better known and managing to attract new practitioners to the sport. The explanation of this theme reflects the need to spread explain and add sport to our culture, bringing its roots and values to our personal spheres. Based on these results, a scenario was built that involves a viable business plan and that in turn can help in the expansion of the sport, a visual identity that adds value to the sport will also be worked, in addition to a product focused on the practice and development of rugby. [resumo fornecido pelo autor]
O rugby é um espore de grande popularidade, mas ainda não conseguiu firmar-se no Brasil, apesar dos números recente que demonstram uma crescente, esta evolução e expansão ainda caminha de forma muito primaria, não explorando toda a capacidade do esporte. Tendo um potencial enorme de crescimento para ser algo a integrar-se a cultura brasileira de desportes. A expansão do esporte visa integrar todas as classes sociais, gêneros e biótipos de todas as idades sendo um esporte perfeito para manter o corpo e mente sadios, além de proporcionar diversão, bem estar, e ajudar no desenvolvimento físico e mental, o esporte oferece um alto grau de competição para os atletas mais enérgicos. Este é um trabalho munido das fermentas do design estratégico e tem por objetivo de difundir e criar uma ponte que aproxime o rugby as pessoas tornando o esporte mais conhecido e conseguindo captar novos praticantes para a modalidade. A explanação deste tema reflete a necessidade de difundir explicar e agregar o esporte a nossa cultura trazendo suas raízes e valores para nossos âmbitos pessoais. Partindo destes resultados foi construído um cenário que envolva um plano de negócios viável e que por sua vez possa ajudar na expansão do esporte, também será trabalhado uma identidade visual que agregue valor a modalidade, além de um produto focado para a prática e desenvolvimento do rugby. [resumo fornecido pelo autor]
Keywords: Rugby; Esporte; Design